Dissemination and implementation science resources, training, and scientific activities provided through CTSA programs nationally: Opportunities to advance D&I research and training capacity. Issue 1 (22nd April 2022) - Shelton, Rachel C.; Dolor, Rowena J.; Tobin, Jonathan; Baumann, Ana; Rohweder, Catherine; Patel, Sapana; Baldwin, Laura-Mae
Abstract: Introduction: Clinical and Translational Science Award (CTSA) Program hubs are well-positioned to advance dissemination and implementation (D&I) research and training capacity nationally, though little is known about what D&I research support and services CTSAs provide. To address this gap, the CTSA Dissemination, Implementation, and Knowledge Transfer Working Group conducted an environmental scan of CTSAs (2017–2018). Methods: Of 67 CTSA institutions, we contacted 43 that previously reported delivering D&I research services. D&I experts from these institutions were emailed a survey assessing D&I resources, services, training, and scientific projects. Responses were categorized and double-coded by study authors using a content analysis approach. Results: Thirty-five of the 43 D&I experts (81.4%) responded. Challenges to CTSAs in developing and supporting D&I science activities were related to inadequate D&I science workforce (45.7%) and lack of understanding of D&I science (25.7%). Services provided included consultation/mentoring programs (68%), pilot funding/grants (50%), and workshops/seminars/conferences (46%). Training and workforce development in D&I were frequently identified as future priorities. Recommendations included increase training to meet demand (68.6%), accessible D&I tools/resources (34.3%), greater visibility/awareness of D&I methods (34.3%), consultation services (22.9%), and expand D&I science workforce (22.9%). Conclusions: CTSAs have tremendous potential to support the advancement and impact of D&I science across the translational continuum. Despite the growing presence of D&I science in CTSAs, continued commitment and prioritization are needed from CTSA and institutional leadership to raise awareness of D&I science and its value, meet training demands, and develop necessary infrastructure for conducting D&I science.